An instrument of peace I shall be (National Justice and Peace Commission, 1986)
UN Year of Peace logo (dove, hands, laurels) Poster advertising peace week organized by the National Justice and Peace Commission (Sri Lanka), 4-11 October, 1986. Featured in the International Peace Poster Exhibition PO-1021